MAPPING THE NEW COMPONENTS OF PEOPLE WITH DISABILITIES IN PUBLIC TRANSPORTATION: SYSTEMATIC LITERATURE REVIEW - Rohmi, Khayu (Universitas Negeri Yogyakarta, 2024)
People with disabilities have long been marginalized in the development process, such as the lack of access to public transportation. However, literature studies on accessibility of persons with disabilities on public transportation are still limited. Therefore, this research aims to produce new components that affect the accessibility of persons with disabilities in public transportation. Sources of research articles are taken based on a 20-year period (2001-2021). The research method used in this study is the Systematic Literature Review (SLR) method. Based on the results of the inclusion criteria that have been used, 45 articles were found that were in accordance with the research topic and were used further in this paper. The results showed that there was a fluctuation in the trend of research on accessibility of persons with disabilities during the 20-year period (2001-2021). Based on the results of the literature mapping, it was found that new components that affect the accessibility of persons with disabilities in public transportation include spatial distribution, technology, situational, socio-economic, and political, vehicle design and service quality. The six elements are related and influence each other. The future research agenda in this study contains several components that can be used as a basis for future research to see the accessibility of persons with disabilities in public transportation.